Contextualization of Prophet Muhammad SAW's Hadith on Humanistic Psychology in Character Building in Indonesia - Saputra, Hasep (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
As a messenger of Allah, the personality of the Prophet Muhammad is very worthy to be emulated, which is reflected in his hadiths, both in the form of his words, deeds and decisions. This article aims to explore the meaning contained in the hadiths of the Prophet Muhammad related to humanistic psychology and then contextualize them with character building in Indonesia. Exploration of meaning is carried out using the Hermeneutics of Hassan Hanafi, in which the hadiths are analyzed historically, eidetically, and practically. This study found that based on a study of the hadiths related to the humanistic psychology of the Prophet Muhammad SAW, character building in Indonesia should be implemented by applying several principles and forms that he has exemplified, namely: 1) given gently and based on compassion, 2) carried out with the aim of providing convenience to others, 3) guiding by providing comfort and pleasure to others, 4) exemplifying and implementing noble morals.